Remembrance, Rebellion, or Racism: Associations between Beliefs about the Confederate Flag’s Symbolism and Political Affiliations, and Racist Attitudes (Journal of Advanced Research in Social Sciences, 2025)
Purpose: this research examines the extent to which beliefs that the Confederate flag stands for remembrance, rebellion, or racism are associated with political affiliations and racial attitudes (Study 1) and patriotism and beliefs about social hierarchies (Study 2). Methods: A nation-wide sample of White adults in the United States were recruited and completed a series of questionnaires about their beliefs about the Confederate flag, political affiliations, and racial attitudes (Study 1, N = 180) and patriotism and beliefs about social hierarchies (Study 2, N = 192). Results: We found that those who believe the Confederate flag stands for remembrance or rebellion had more positive feelings about the flag, had more conservative beliefs, were more patriotic, had more negative attitudes toward Black Americans, and were more likely to adhere to beliefs about social hierarchies. Implications: Findings of these studies have important implications for race relations in the United States.